2020
DOI: 10.1080/22423982.2020.1798113
|View full text |Cite
|
Sign up to set email alerts
|

It’s about being the good parent: exploring attitudes and beliefs towards active school transportation

Abstract: In recent decades, there has been a decline in active school transportation (AST). Parents play an important role as the key decision-makers of children's AST, and there is a need of more knowledge about the decision-making process and parents' beliefs towards AST. The overall aim of this study was to explore parents' attitudes and beliefs towards AST in the northern part of Sweden. Twenty parents participated in semi-structured interviews, which was based on the theory of planned behaviour. Qualitative conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…In their review, Rivis and Sheeran suggested that descriptive norms are more likely to be important when it comes to behaviors that involve risk [ 27 ]. In addition, our previous results from a qualitative study showed that being perceived as a “good parent” in the eyes of significant others was important to parents [ 33 ]. Parents explained that being a “good parent” could potentially be in conflict with AST, because it would include not exposing their children to risks, which consequently would lead to significant others considering them as irresponsible parents.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In their review, Rivis and Sheeran suggested that descriptive norms are more likely to be important when it comes to behaviors that involve risk [ 27 ]. In addition, our previous results from a qualitative study showed that being perceived as a “good parent” in the eyes of significant others was important to parents [ 33 ]. Parents explained that being a “good parent” could potentially be in conflict with AST, because it would include not exposing their children to risks, which consequently would lead to significant others considering them as irresponsible parents.…”
Section: Discussionmentioning
confidence: 99%
“…Parents explained that being a “good parent” could potentially be in conflict with AST, because it would include not exposing their children to risks, which consequently would lead to significant others considering them as irresponsible parents. On the other hand, the qualitative study also showed that if parents perceived that significant others allowed their child to use AST, they became more inclined to do the same [ 33 ]. Our results support those of Pang et al [ 23 ], who concluded that it might be efficient to put effort into changing social norms to alter these kinds of intentions in parents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations